Use of the prognostic nutrition index as a predictive biomarker in small-cell lung cancer patients undergoing immune checkpoint inhibitor treatment in the Chinese alpine region - Wu, Yunjiao; Yang, Jing; Qiao, Xinyi; Li, Yingjie; Zhao, Rui; Lin, Tie; Li, Xiaoli; Wang, Meng (Frontiers in Oncology, 2023)
Background Whether the prognostic nutritional index (PNI), which is suggested to reflect systemic inflammation and nutritional status of patients, could be used as an effective prognostic factor for small-cell lung cancer (SCLC) has not yet been clarified. The purpose of this study was to verify the prognostic value of the PNI in SCLC patients treated with programmed cell death ligand-1/programmed cell death 1 (PD-L1/PD-1) inhibitors in the alpine region of China. Methods SCLC patients treated with PD-L1/PD-1 inhibitors monotherapy or combined with chemotherapy between March 2017 and May 2020 were included. Based on the values of serum albumin and total lymphocyte count, the study population was divided into two groups: high and low PNI. The Kaplan-Meier method was used to compute the median survival time and the log-rank test was used to compare the two groups. To evaluate the prognostic value of the PNI, univariable and multivariable analyses of progression-free survival (PFS) and overall survival (OS) were performed. The correlations between PNI and DCR or ORR were calculated by Point biserial correlation analysis. Results One hundred and forty patients were included in this study, of which, 60.0% were high PNI (PNI > 49.43) and 40.0% were low PNI (PNI ≤ 49.43). Results indicated that the high PNI group had better PFS and OS than the low PNI group in the patients who received PD-L1/PD-1 inhibitors monotherapy (median PFS: 11.0 vs. 4.8 months, p < 0.001 and median OS: 18.5 vs. 11.0 months, p = 0.004). Similarly, better PFS and OS were associated with an increase in PNI level in the patients who accepted PD-L1/PD-1 inhibitors combined with chemotherapy (median PFS: 11.0 vs. 5.3 months, p < 0.001 and median OS: 17.9 vs. 12.6 months, p = 0.005). Multivariate Cox-regression model showed that high PNI was significantly related to better PFS and OS in patients who accepted PD-L1/PD-1 inhibitors monotherapy or combined with chemotherapy (PD-L1/PD-1 inhibitors monotherapy: PFS: HR = 0.23, 95% CI: 0.10–0.52, p < 0.001 and OS: HR = 0.13, 95% CI: 0.03–0.55, p = 0.006; PD-L1/PD-1 inhibitors combined with chemotherapy: PFS: HR = 0.34, 95% CI: 0.19–0.61, p < 0.001 and OS: HR = 0.53, 95% CI: 0.29–0.97, p = 0.040, respectively). Additionally, Point biserial correlation analysis between PNI and disease control rate (DCR) showed that PNI status was positively correlated with DCR in SCLC patients receiving PD-L1/PD-1 inhibitors or combined with chemotherapy (r = 0.351, p < 0.001; r = 0.285, p < 0.001, respectively). Concussions PNI may be a promising biomarker of treatment efficacy and prognosis in SCLC patients treated with PD-L1/PD-1 inhibitors in the alpine region of China.